PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 1 KABUN - Tanjung, Faisal Amri; Musdi, Edwin (Departemen Matematika, 2024)
Mathematics learning outcomes can be said to be successful if someone is able to recognize and master mathematics subject matter in learning activities. However, in reality, learning mathematics often results in low learning outcomes. Students at SMP Negeri 1 Kabun can also suffer from low mathematics learning outcomes. Regarding this problem, the solution offered in this research is the Two Stay Two Stay (TSTS) learning model. In this research, the aim is to convey mathematics learning outcomes by comparing students who implemented it using the TSTS learning model and students who implemented it using the direct learning model at SMP Negeri 1 Kabun. In this research, using a quasi-experiment as a type of research by choosing a nonequivalent posttest only control group design as the research design. To conduct this research, Class IX of SMP Negeri 1 Kabun became the population using the Purposive Sampling technique for sampling. Class IX-4 was selected as the experimental group and Class IX-3 was selected as the control group. Minitab software was used to analyze the final test results. The results obtained with a P-value <0.05 indicate that students at SMP Negeri 1 Kabun who apply TSTS learning get superior mathematics learning outcomes compared to students who apply direct learning. Therefore, there is a significant difference in mathematics learning outcomes between students at SMP Negeri 1 Kabun who take TSTS learning and those who take direct learning.Keywords – Two Stay Two Stray, Learning Outcomes